Card Games and Algebra Tic Tacmatics on Achievement of Junior Secondary II Students in Algebraic Expressions - Okpube Nnaemeka Michael; N. M. Anugwo (Institute of Advanced Engineering and Science, 2016)
This study investigated the Card Games and Algebra tic-Tacmatics on Junior Secondary II Students’ Achievement in Algebraic Expressions. Three research questions and three null hypotheses guided the study. The study adopted the pre-test, post-test control group design. A total of two hundred and forty (240) Junior Secondary School II students were used as sample for this study. The experimental group was taught using games while the control group was taught using the conventional (lecture) method. Algebraic Achievement Test (AAT) was used to collect data for this study. AAT was validated by three experts in mathematics education and measurement and evaluation respectively. The reliability index of AAT was 0.79. Mean and standard deviation were used to answer the research questions while ANCOVA was used to test the hypotheses at 0.05 level of significance. The findings of the study showed among others that there was a significant difference between students taught algebraic expressions with games and those taught without games, there was also a significant difference between the achievement of males and females taught algebraic expressions with games and those taught without games in favour of the males.